Pengungkapan Laporan Keuangan di Jakarta Islamic Index - Yohanna Thresia Nainggolan (LPPM Universitas Bina Sarana Informatika, 2023)
In this modern economic era, there are industries that do not practice transparent disclosure of financial information. The purpose of this study was to determine the effect of profitability and liquidity on financial statement disclosures in the Jakarta Islamic Index. The population in this study is 48 companies at JII in the 2018–2021 period. The sample size was determined using a purposive sampling method based on certain criteria, consisting of 12 companies for a 4-year study (2018–2021). The data collected is (n) = 4 x 12 = 48. The coefficient of determination is 0.423, which means that the ability of the independent variable to explain the dependent variable is 42.3% and the remaining 57.7% is influenced by other factors not included in the regression model. Based on the results of the F test regression analysis, it shows that profitability (ROA) and liquidity (CR) simultaneously affect financial statement disclosure. Based on the results of the t-test regression analysis, it shows that profitability (ROA) has a negative and significant effect and liquidity (CR) has no significant effect on financial statement disclosure. Keywords: Disclosure of Financial Statements, Profitability, and Liquidity